(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This paper explores the role of Mobile-Assisted Language Learning (MALL) in the context of English language education. Drawing on recent research, it outlines the key benefits of MALL, including flexibility, learner autonomy, personalization, and access to authentic materials. The study also discusses significant challenges such as the digital divide, limited teacher readiness, and assessment difficulties. Recommendations are provided to enhance MALL integration through teacher training, equitable access, and curriculum alignment. Overall, MALL is positioned as an innovative and learner-centered approach that supports 21st-century language education goals.